Natural history of MYH7-related dilated cardiomyopathy. (3rd October 2022) - Frutos Seminario, F; Ochoa, J P; Navarro-Penalver, M; Baas, A; Bjerre, J V; Zorio, E; Mendez, I; Lorca, R; Verdonschot, J A J; Garcia-Granja, P E; Bilinska, Z; Fatkin, D; et al.
Abstract: Background: Variants in MYH7 are responsible for disease in 1–5% of patients with dilated cardiomyopathy (DCM); however, the clinical characteristics and natural history of MYH7-related DCM are poorly described. Objectives: We sought to determine the phenotype and prognosis of MYH7-related DCM. We also evaluated the influence of variant location on phenotypic expression. Methods: We studied clinical data from 147 individuals with DCM-causing MYH7 variants (47.6% females, 35.6±19.2 years) recruited from 29 international centers. Results: At initial evaluation, 106 patients (72.1%) had DCM (LVEF 34.5±11.7%). Median follow-up was 4.5 years (interquartile range: 1.7–8.0). 23.7% carriers who were initially phenotype-negative developed DCM. Disease penetrance by 40 and 60 years was 46% and 88%, respectively, with 18 patients (16%) first diagnosed at <18 years. Thirty-six percent of patients with DCM met imaging criteria for LV non-compaction. During follow-up, 28% showed left ventricular reverse remodeling (LVRR). Overall incidence of end-stage heart failure (heart transplantation or heart failure related death) was 11.6% at 5 years. Overall major ventricular arrhythmia rate was low (1.0% at 5 years) even among patients with LVEF ≤35% (2.1% at 5 years). LV non-compaction was more prevalent in patients with variants in head domain (S1) (44.2%) compared with other domains (P<0.001). No differences among domain groups were found regarding LVRR, major ventricular arrhythmias or end-stage heart failure. Conclusions: MYH7-related DCM is characterized by early age of onset, high penetrance, low rate of LVRR, and frequent progression to ESHF. Heart failure complications predominate over ventricular arrhythmias, even among patients with severe systolic disfunction. Funding Acknowledgement: Type of funding sources: None.